Researching Together: A CTSA Partnership of Academicians and Communities for Translation. Issue 5 (3rd June 2013) - Westfall, John M.; Nearing, Kathryn; Felzien, Maret; Green, Larry; Calonge, Ned; Pineda‐Reyes, Fernando; Jones, Grant; Tamez, Montelle; Miller, Sara; Kramer, Andrew
Abstract: Background: The Colorado Clinical and Translational Sciences Institute (CCTSI) aims to translate discovery into clinical practice. The Partnership of Academicians and Communities for Translation (PACT) represents a robust campus–community partnership. Methods: The CCTSI collected data on all PACT activities including meeting notes, staff activity logs, stakeholder surveys and interviews, and several key component in‐depth evaluations. Data analysis by Evaluation and Community Engagement Core and PACT Council members identified critical shifts that changed the trajectory of community engagement efforts. Results: Ten "critical shifts" in six broad rubrics created change in the PACT. Critical shifts were decision points in the development of the PACT that represented quantitative and qualitative changes in the work and trajectory. Critical shifts occurred in PACT management and leadership, financial control and resource allocation, and membership and voice. Discussion: The development of a campus–community partnership is not a smooth linear path. Incremental changes lead to major decision points that represent an opportunity for critical shifts in developmental trajectory. We provide an enlightening, yet cautionary, tale to others considering a campus–community partnership so they may prepare for crucial decisions and critical shifts. The PACT serves as a genuine foundational platform for dynamic research efforts aimed at eliminating health disparities.